1997
DOI: 10.1148/radiology.204.1.9205242
|View full text |Cite
|
Sign up to set email alerts
|

Shin splints: MR appearance in a preliminary study.

Abstract: Patients with acute shin splints have a spectrum of MR findings, which suggests this clinical entity is part of a continuum of stress response in bone. The strong association between chronic symptoms and a normal-appearing MR image implies that this modality has less utility in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 0 publications
0
38
1
1
Order By: Relevance
“…Therefore, the tibiae showing localized focal uptake but not linear uptake of technetium 99m were diagnosed as having a stress fracture. Patients with acute shin splints have a spectrum of MR findings (normal appearance, periosteal fluid only, abnormal marrow signal intensity, and stress fracture), which suggests this clinical entity is part of a continuum of stress response in bone [16] . However, the strong association between chronic symptoms and a normal-appearing MR image implies that this modality has less utility in these patients [16] .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the tibiae showing localized focal uptake but not linear uptake of technetium 99m were diagnosed as having a stress fracture. Patients with acute shin splints have a spectrum of MR findings (normal appearance, periosteal fluid only, abnormal marrow signal intensity, and stress fracture), which suggests this clinical entity is part of a continuum of stress response in bone [16] . However, the strong association between chronic symptoms and a normal-appearing MR image implies that this modality has less utility in these patients [16] .…”
Section: Methodsmentioning
confidence: 99%
“…13 The activityrelated lower leg pain is typically associated with diffuse tenderness along the posteromedial tibia in its middle to distal aspect and various terms such as shin splints syndrome, soleus syndrome, and medial tibial stress syndrome have been applied to describe this. 27,28 Four MRI patterns have been described in two different studies by Anderson et al 29 and Fredericson et al, 17 who demonstrated a continuum of changes on MRI images in patients with activity-related leg pain, including (1) normal appearance, (2) periosteal fluid, (3) bone marrow oedema, and (4) stress fracture, all of which concurred with findings on bone scintigraphy. These studies concluded that MRI (Fig.…”
Section: Imaging Optionsmentioning
confidence: 75%
“…Some authors suggest an inflammation of the periosteum due to excessive traction (traction theory), others support the view that MTSS is not an inflammatory process of the periosteum, but rather a bone stress reaction (bone stress theory) as in stress fractures [23][24][25]. Although that MTSS and stress fractures constitute different pathologies, they sometimes coexist and it is likely that MTSS and stress fractures of the tibia are invoked by similar mechanisms, where MTSS is a relatively mild expression and stress fracture is a severe extreme [1].…”
Section: Discussionmentioning
confidence: 99%